THE EFFECTS OF DIFFERENT IMMERSION METHOD AND TIME ON THE PHYSICO-CHEMICAL CHARACTERISTICS OF SKIPJACK TUNA (Katsuwonus pelamis) FISH MEAL - Christina Litaay; Joko Santoso (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
High fat content in a dark fleshed fish can affect on nutritional value because it can lead to odors in fish meal products. Effort Immersion (deffating) is one way to reduce fat content in fish meal products in order to reduce the products from odor. Research on methods and durations of immersion effects were conducted from October to November 2011. This study aimed to determine the best method to get quality materials skipjact tuna fish meal based on methods and durations of immersion. Fish sampling were taken from the village of Latuhalat, Ambon-Maluku waters. Deffating process used water, 3% acetic acid, and 0.8% sodium bicarbonate. Immersion durations were 2, 4, and 6 hours. Deffating method using 0.8% sodium bicarbonate with 6 hours immersion time exhibited the best quality fish meal with protein content of 82.86% and 1.10% fat content. Keywords: deffating, fish meal, skipjact tuna.